Mesenteric Venous Thrombosis in Early Pregnancy - Maghsoudi, Leila H.; Pak, Haleh (Current Women's Health Reviews, 2022)
Background: Acute abdominal due to primary mesenteric venous thrombosis is uncommon during pregnancy. Case presentation: This is a case presentation of a 23-year-old pregnant woman with a personal history of immune thrombocytopenia and splenectomy performed 4 years ago, who presented at the emergency department with abdominal pain, nausea, vomiting, and diarrhea. The patient underwent resection and anastomosis of gangrene in the small intestine due to mesenteric venous ischemia. Conclusions: The diagnosis of mesenteric venous thrombosis should be considered in the setting of acute abdomen in early pregnancy in women with prior history of coagulation disorder.
Keywords: mesenteric venous thrombosis